Rice markets, agricultural growth, and policy options in Viet Nam - Goletti, Francesco; Minot, Nicholas (International Food Policy Research Institute, 1997)
Viet Nam has undergone a profound transformation in recent years and, as a result of a series of macroeconomic and institutional reforms since 1986, it has made substantial progress toward becoming a market economy. As this transition continues, Viet Nam faces the challenge of formulating and implementing a growth strategy which is both economically and politically feasible. Critical to this growth strategy is the role of agriculture and, within agriculture, the development of an efficient rice marketing system. The emergence of Viet Nam as a major rice exporter has raised a number of important policy questions. First, will the country be able to continue its impressive growth? Second, how far has Viet Nam moved along the path toward a market economy? Third, what is the role of the government in the development of a rice market economy? Finally, what is the best way to promote food security? The paper addresses these issues and report the results of a study conducted by IFPRI for the Asian Development Bank in collaboration with the Ministry of Agriculture and Rural Development of the Government of Viet Nam. The study is based on extensive data collection from marketing agents (farmers, traders, millers, state owned enterprises, and exporters) conducted during 1995 and 1996.